2002
DOI: 10.1038/emm.2002.29
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Fas cross-linking on phospholipase D activation and related lipid metabolism in Fas-resistant A20 cells

Abstract: A20 murine lymphoma cells undergoing Fas-mediated apoptosis showed increase in the activity of phospholipase D (PLD), which is involved in proliferative or mitogenic cellular responses. Using A20 cell lines that were resistant to Fas-induced apoptosis, we investigated the differential effects of Fas cross-linking on PLD activity and sphingolipid metabolism. The basal PLD activities in all of the selected three Fasresistant clones (#5, #8, and #11) were about 2~4 folds higher than that of wild type A20 cells. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…PLD activity was determined by measuring the [ 3 H]-PBt produced via PLD catalyzed transphosphatidylation in [ 3 H]-palmitic acid labeled cells (Lim et al, 2002). MIN6N8 cells were radioactively labeled overnight with 2 μCi/ml of [ 3 H] palmitic acid in medium, and then pretreated with 0.3% (v/v) 1-butanol for 15 min before stimulation with glucose.…”
Section: Determination Of Pld Activitymentioning
confidence: 99%
“…PLD activity was determined by measuring the [ 3 H]-PBt produced via PLD catalyzed transphosphatidylation in [ 3 H]-palmitic acid labeled cells (Lim et al, 2002). MIN6N8 cells were radioactively labeled overnight with 2 μCi/ml of [ 3 H] palmitic acid in medium, and then pretreated with 0.3% (v/v) 1-butanol for 15 min before stimulation with glucose.…”
Section: Determination Of Pld Activitymentioning
confidence: 99%
“…On the other hand, cancerous cells can develop their own mechanism to escape from Fas‐mediated cell death [Lim et al, 2002; Kongphanich et al, 2002]. Earlier, we cloned Fas‐resistant A20 cells (FasR) from wild‐type murine B lymphoma A20 cells [Lim et al, 2002], and the FasR clone showed increased resistance against Fas‐induced apoptosis.…”
mentioning
confidence: 99%
“…On the other hand, cancerous cells can develop their own mechanism to escape from Fas‐mediated cell death [Lim et al, 2002; Kongphanich et al, 2002]. Earlier, we cloned Fas‐resistant A20 cells (FasR) from wild‐type murine B lymphoma A20 cells [Lim et al, 2002], and the FasR clone showed increased resistance against Fas‐induced apoptosis. The isolation of FasR promoted us to elucidate the signaling pathways for anti‐apoptosis and cell survival, and to identify crucial component involved in resistance against Fas‐induced apoptotic signals; basal PLD activity of FasR was higher than that of wild‐type A20 cells, which was found to be due to PLD2 overexpression [Lim et al, 2002].…”
mentioning
confidence: 99%
“…In some cells phosphatidylcholine hydrolysis has been reported to increase during apoptosis [23][24][25], whereas in others PLD activity has been reported to decrease [26][27][28]. Furthermore, inhibiting PLD activity can initiate apoptosis [29,30] with over-expression of PLD1 or PLD2 protecting various cancerous cells from apoptosis [31][32][33][34], possibly via mechanisms that stabilises p53 via activation of mToR [35,36] and/or Raf1 or Ral [33].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inhibiting PLD activity can initiate apoptosis [29,30] with over-expression of PLD1 or PLD2 protecting various cancerous cells from apoptosis [31][32][33][34], possibly via mechanisms that stabilises p53 via activation of mToR [35,36] and/or Raf1 or Ral [33]. Thus PLD-based signalling is most likely to be prosurvival and anti-apoptotic [1][2][3][25][26][27][28][29][30][31][32][33][34][35]. It is possible that PLD represents a legitimate target for the apoptotic machinery to enable plasma membrane remodelling [2] and necessary disruption of the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%